1998
DOI: 10.1083/jcb.142.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Dual Actions of Sphingosine-1-Phosphate: Extracellular through the Gi-coupled Receptor Edg-1 and Intracellular to Regulate Proliferation and Survival

Abstract: Sphingosine-1-phosphate (SPP), a bioactive lipid, acts both intracellularly and extracellularly to cause pleiotropic biological responses. Recently, we identified SPP as a ligand for the G protein–coupled receptor Edg-1 (Lee, M.-J., J.R. Van Brocklyn, S. Thangada, C.H. Liu, A.R. Hand, R. Menzeleev, S. Spiegel, and T. Hla. 1998. Science. 279:1552–1555). Edg-1 binds SPP with remarkable specificity as only sphinganine-1-phosphate displaced radiolabeled SPP, while other sphingolipids did not. Binding of SPP to Edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
437
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(467 citation statements)
references
References 64 publications
27
437
2
1
Order By: Relevance
“…Similar results were published by Van Brocklyn et al [24], who could demonstrate that S1P at high concentrations acts not necessarily through binding to S1P receptors, but rather following cellular uptake of the phospho-lipid. Mononuclear phagocytes mainly express two S1P receptors, S1P 1 and S1P 2 [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were published by Van Brocklyn et al [24], who could demonstrate that S1P at high concentrations acts not necessarily through binding to S1P receptors, but rather following cellular uptake of the phospho-lipid. Mononuclear phagocytes mainly express two S1P receptors, S1P 1 and S1P 2 [12].…”
Section: Discussionsupporting
confidence: 89%
“…3 and 6). S1P is a unique signaling molecule in that it can act both as an extracellular ligand for G protein-coupled receptors and as an intracellular second messenger [11,[24][25][26]. A few studies have suggested that suppression of apoptosis by S1P is mediated via its intracellular action, many others have argued in favor of the involvement of S1P membrane receptors, making this a controversial area (for review, see Hla et al [27]).…”
mentioning
confidence: 99%
“…In previous studies, in fibroblasts [6,31], the intracellular mechanisms have been proposed for S1P action on cell proliferation. Our results, however, favour the extracellular mechanism, through S1P receptors, for the S1P-induced actions on the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…100 nM), although the magnitude of the activity without FBS, regardless of the presence of S1P, was about one-third of the activity with FBS (results not shown). We also examined the effects of dihydrosphingosine 1-phosphate, which is thought to be an agonist for S1P receptors [31]. We found that the S1P derivative mimicked the S1P-induced actions…”
Section: S1p Induces Dna Synthesis and Migration Of Endothelial Cellsmentioning
confidence: 99%
“…Subsequent studies established that at least in chordates and mammals, S1P act as extracellular ligands for a family of G-protein coupled receptors called S1P receptors [152][153][154]. In mammals, S1P executes most of its extracellular functions by engaging these receptors.…”
Section: Overview Of S1p Family Of Receptorsmentioning
confidence: 99%